Penilaian Kualitas Hidup Pasien Pasca Bedah Pintas Koroner Yang Menjalani Rehabilitasi Fase III - Kiki Abdurachim; Harmani Kalim; Basuni Radi (The Indonesian Heart Association, 2007)
Background. Coronary artery bypass graft surgery (CABG) is one of the management for coronary artery disease. Cardiovascular rehabilitation usually conducted for recovery and improved quality of life. Questionnaire was used to evaluate quality of life. One of the quality of life instrument most commonly used is Questionnaire SF-36. So far there isn’t any study to evaluate quality of life in patients post CABG who wish to follow rehabilitation program phase III in Indonesia.Methods and results.This is a cross sectional study conducted in the National Cardiovascular Centre (NCC) - Rehabilitation Division to patients post CABG in phase III rehabilitation program during 2004-2005. Subject was taken in consecutive sampling manner. Questionnaire SF-36 was handed directly or via mail. Validity and reliability test was done for the questionnaire form in Indonesia language. There were 112 patients, 34 patients did rehabilitation program in hospital and 78 were home-based. The characteristics between two groups were similar. Validity test using r product moment from Pearson to every questions in SF-36 showed r = 0,53-0.83 > 0,51 (r table) and Cronbach a= 0,855. SF-36 scoring was not significantly different among the two groups (in hospital rehab vs home-based rehab) and also control group (healthy). Conclusions. There were no difference in quality of life and aerobic ca-pacity in patients who performed rehabilitation program phase III in hospi-tal and home-based.